Oral language and pre-reading skills in children of four to six years. A study on marginality and bilingualism in peru - Canales Gabriel, Ricardo (2014)
The purpose of the study was to determine if the condition of marginality and bilingualism could be affecting proper oral linguistic development and pre reading skills in children aged 4-6 years children of three areas of Perú, and also establish the correlation between the level of development of the components phonological, morph- syntactic and semantic oral language, phonological awareness, verbal short-term memory and other pre-reading skills. For this purpose, urban children was examined children initial education of urban areas: Lima and Ate- Vitarte, and rural areas: Spanish monolingual: Cajamarca and bilingual: Huancavelica, with the short test bilingualism (Escobar 1978 , González 2006), Test ELO of Ramos (2008) and Test BIL 3-6 ( Battery start reading ) of Selles (2008). The results showed significant differences in oral language development between groups for urban children. Children in bilingual status - rural marginality: Huancaveliv: Quintaojo, and secondly, children: Cajamrca: Huayobamba, obtained lower yields. A similar result is seen with respect to the pre- reading skills. Significant correlation was found between the levels of development between the various aspects of oral language with pre reading skills.